Strategier på en dynamisk marknad - Borg, Jennie (2008)
Garden center and market gardens are a growing trade, undergoing great changes with new actors and purchasing habits. The interest in gardens and plants is steadily increasing, official statistics show an increase of garden plants and flower consumption, of an annual 3 per cent. Garden centers and market gardens are in great need of development to be able to tackle the prevailing competition, and maintain a steady growth. Many companies are heading for a generation shift and are founding it difficult to find and employ younger managers. The aim of this report is to examine different strategies of garden centers and market gardens through the manager/ owner's views and opinions about competition, growth and success. Michael Porter's strategic framework, the five forces and the generic strategies of cost leadership, differentiation and focusing, have been used in the analysis. This has been accomplished with the help of observations and personal interviews. Retail studies have been carried out with the help of a standardized and categorized schedule, where all interesting types of behavior and impressions have been registered. The retail studies have been made in 30 different garden centers and market gardens in the Scania district in southern Sweden. The personal in depth interviews have been carried out with ten managers/ owners in the garden center and market garden trade. The chosen companies have little in common, primarily in order set to a wider spectrum as well as to be able to make a comparison between them. The trade has a strength and competitive advantage in its qualified staff. Knowledge of the trade can help employers offer a higher service level, compared to competitors like food retailers and home equipment stores. The results of the interviews show that the trade is characterized by of garden center and market garden owners with a great deal of personal commitment. Several responders refer to the company and its production as being a lifestyle, and they take great pride in their work. Even though they work extremely hard, most of them state that they are satisfied with their working situation. The results of the interviews also show that the prospects within the trade are overall positive. Differentiation may be the most advantageous strategy for survival on the market. The small, privately run garden centers and market gardens can thereby distinguish themselves from the bigger actors on the market. It is important to be able to offer a unique product, service, quality, brand, accessory or experience.